Paper money collapse : the folly of elastic money - Schlichter, Detlev S., 1964- (Hoboken : Wiley, 2014)
'Explore the inevitable collapse of the fiat monetary systemPaper Money Collapse: The Folly of Elastic Money and the Coming Monetary Breakdown, Second Edition challenges the mainstream consensus on money and monetary policy. While it is today generally believed that the transition from'hard' and inflexible commodity money (such as a gold standard) to entirely flexible and potentially unlimited fiat money under national central banks allows for superior economic stability, Paper Money Collapse shows that the opposite is true. Systems of highly elastic and constantly expanding money are not only unnecessary, even for growing economies, they are always extremely destabilizing. Over time, they must lead to substantial imbalances, including excessive levels of debt and distorted asset prices, that will require ever faster money production to sustain. Ultimately, however, there is no alternative to a complete liquidation of these distortions. Based on insights of many renowned economists and in particular of the Austrian School of Economics, the book explains through rigorous logic and in precise language why our system of flexible fiat money is incompatible with a market economy and therefore unsustainable. Paper money systems have always led to economic disintegration--without exception--throughout history. It will not be different for our system and we may be closer to the endgame than many think.The updated second edition incorporates: A new introduction and an extended outlook section that discusses various'endgames' Responses to criticisms, alternative views, and a critical assessment of'solutions' Comments on recent policy trends, including attempts to exit the'easy money' policy mode An evaluation of new crypto-currency Bitcoin Paper Money Collapse: The Folly of Elastic Money, Second Edition clarifies the problem of paper money clearly and eloquently, and proposes multiple routes to a solution'--
'This book illustrates the underlying problems with elastic money'--
Machine generated contents note: Foreword Acknowledgments Prologue: Contra the Mainstream Consensus -- What this book is about The Ruling Mainstream Consensus on Money The Growth-versus-inflation Trade Off What This Book Will Show Understanding Our Fiat Money System What is Different from the First Edition? Support from Eminent Economists Notes Part One: The Basics of Money Chapter 1 The Fundamentals of Money and Money Demand The Origin and Purpose of Money An Anthropologist's Challenge What Gives Money Value? (Almost) Any Quantity of Money Will Do The Demand for Money Are'Sticky' Prices a Problem? Other Functions of Money The Unique Position of the Paper Money Producer The Monetary Asset versus Other Goods Notes Chapter 2 The Fundamentals of Fractional-Reserve Banking The Origin and Basics of Fractional-Reserve Banking Who Owns'Deposited' Money? Exposing Misconceptions about Fractional-Reserve Banking'Free Banking' is Limited Banking Summary of Part One Notes Part Two: The Effects of Money Injections Chapter 3 Money Injections without Credit Markets Even, Instant, and Transparent Money Injection Even and Nontransparent Money Injection Uneven and Nontransparent Money Injection Notes Chapter 4 Money Injections via Credit Markets Consumption, Saving, and Investing Interest Interest Rates are Not Determined by Factor Productivity Money Injection via the Loan Market The Process in More Detail Policy Implications of the Austrian Theory Addendum: Gordon Tullock's Critique of the Austrian Business Cycle Theory and some words on'forced saving' An Example: U.S. Housing Boom and Bust Summary of Part Two Notes Part Three: Fallacies about the Price Level and Price Level Stabilization Chapter 5 Common Misconceptions Regarding the Price Level The Fallacy that a Stable Price Level Means'Neutral' Money The Fallacy that Hard Money is Unstable Money, Part 1 -- History The Fallacy that Hard Money is Unstable Money, Part 2 -- Theory Notes Chapter 6 The Policy of Stabilization Problems with Price Index Stabilization Addendum: The'Free Bankers' and the Theory of Immaculate Fractional-Reserve Banking Summary of Part Three Notes Part Four: A History of Paper Money and How We Got to Where We Are Now Chapter 7 A Legacy of Failure Paper Money Experiments 1914 -- 2014 -- A Century of Monetary Decay Notes Part Five: Beyond the Cycle -- Paper Money's Endgame and The Future of Money Chapter 8 The Beneficiaries of the Paper Money System Paper Money and the Banks Paper Money and the State Paper Money and the Professional Economist Notes Chapter 9 The Intellectual Superstructure of the Present System The Alternative View: Individualism and Laissez-Faire The Mainstream View: Collectivism and Interventionism The Political Appeal of Mainstream Macroeconomics The Myth That Everybody Benefits from'Stimulus' Monetarism as Monetary Interventionism The Savings Glut Theory and the Myth of Underconsumption and Underinvestment Inflationism and International Policy Coordination Notes Chapter 10 Endgames -- Inflationary Meltdown or Return to Hard Money? Paper Money Collapse Alternatives: Return to Hard Money A Return to a Gold Standard The Separation of Money and State Bitcoin -- Money of No Authority Notes Epilogue: Money, Freedom, and Capitalism About the Author Index .
Includes bibliographical references and index.
Keywords: Paper money; Money supply; Currency question; Credit